Only When They're Little - Day, Kate Pickens (Appalachian State University, 1985)
A fictional account of an actual family whose Scotch-Irish ancestors immigrated to western North Carolina in the early nineteenth century, Only When They're Little is an authentic tale of Kate Pickens Day's family life near Asheville, North Carolina. Published in 1985, this book combats the stereotype of the impoverished mountain people by presenting a new narrative. A middle class family living in a fictional town near Asheville named "Tarpley," the book centers on an energetic and well educated woman named Cora Barker. Devoted to helping each of her family members excel in their chosen activity, this book is filled with drama, hardship, and the importance of being a good person.